Pengaruh Pelatihan Kerja, Motivasi Kerja Dan Kedisiplinan Kerja Terhadap Kinerja Karyawan Pada PT. Rezeki Surya Intimakmur - Samuel Agung Hutauruk; Josua Pratama Nababan; Rosinta Romauli Situmeang; Lastiar Nurcahaya Sinaga (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of the study was to determine the effect of job training, work motivation and work discipline on employee performance at PT. Surya Intimakmur's sustenance. The research is descriptive quantitative. The total population in this study was 150 people, so that a sample of 25% of the population was taken as many as 38 people. The independent variables consist of job training (X1), work motivation (X2) and work discipline (X3), while the dependent variable is employee performance. The data in this study were analyzed by multiple linear regression test. The results of the study revealed that training, work motivation, and work discipline all had a significant impact on employee performance partially and simultaneously at PT. Surya Intimakmur's sustenance. The results showed that the variables of training, work motivation and work discipline explained their effect on employee performance at PT. Surya Intimakmur's sustenance is 79.60%. The remaining 20.40% is caused by the influence of unmeasured independent factors such as work environment variables, leadership style, compensation and incentives, and various other variables. Keywords: Job Training, Work Motivation, Work Discipline and Performance